Clinical Evaluation of Fiducial Marker Pre-Planning for Virtual Bronchoscopic Navigation Implantation in Lung Tumour Patients Treated With CyberKnife - Ku, Ki Man; Lam, Bing; Wu, Vincent W. C.; Chan, Kwok Ting; Chan, Chloe Y. Y.; Cheng, H. C.; Yuen, Kamy M. Y.; Cai, Jing (Frontiers in Oncology, 2022)
Abstract Purpose: For the treatment of invisible lung tumours with CyberKnife (CK), fiducial markers (FMs) were implanted as an internal surrogate under Virtual Bronchoscopic Navigation (VBN). This research aims to study the benefits of introducing an additional procedure in assigning the optimal FM positions using a pre-procedure planning system and performing virtual simulation before implantation. The objectives are 1) To reduce the duration of FMs implantation procedure; 2) to reduce the radiation exposure in Dose Area Product (DAP) (dGy*cm^2) to patients; and 3) to increase the number of FMs implanted around the tumour. Methods and Materials: This study is retrospective, single-centre and observational in nature. 32 patients were divided into two groups. 18 Group 1 patients underwent conventional VBN FM implantation. 14 Group 2 patients underwent additional pre-procedure planning and simulation. The steps of pre-procedure planning include 1) importing CT images into the treatment planning system (Eclipse, Varian Medical System, Inc.) and delineating five to six FMs in their ideal virtual positions. 2) copy the FM configuration into VBN planning software (LungPoint Bronchus Medical, Inc.) for verification and simulation. Finally, the verified FMs were deployed through VBN with the guidance of the LungPoint planning software. Results: 162 FMs were implanted among 35 lesions in 32 patients aged from 37 to 92 (Median=66). 16 males, and 16 females. Results showed that 1) the average FM insertion time was shortened from 41 minutes (SD=2.05) to 23 minutes (SD=1.25), p=0.00; 2) the average absorbed dose of patients in DAP was decreased from 67.4 cGy*cm^2 (SD=14.48) to 25.3 cGy*cm^2 (SD=3.82), p=0.01 (1 tail); and 3) the average number of FMs implanted around the tumour was increased from 4.7 (SD=0.84) to 5.6 (SD=0.76), p=0.00 (1 tail). Conclusion: The pre-procedure planning reduces the FMs implantation duration from 41.1 minutes to 22.9 minutes, reduces the radiation exposure in DAP from 67.4 to 25.3 dGy*cm^2, and increases the number of FMs inserted around the tumour from 4.7 to 5.6.